2022
DOI: 10.3390/cells12010141
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic CD8+ T Cells Are Involved in the Thrombo-Inflammatory Response during First-Diagnosed Atrial Fibrillation

Abstract: Background: Atrial myopathy and atrial fibrillation (AF) accompany thrombo-inflammation. This facilitates disease progression and promotes major adverse cardiovascular events (MACEs). Thrombin receptor (protease-activated receptor 1, PAR1) signalling is central in mediating thrombo-inflammation. We hypothesised that PAR1 signalling links coagulation and inflammation through cytotoxic CD8+ T lymphocytes in patients presenting with first-diagnosed AF (FDAF). Methods: A total of 210 patients were studied. We incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…In an observational study of 100 consecutive patients, including 80 patients with a first diagnosis of AF and 20 control patients, it was found that pro-inflammatory and cytotoxic T-lymphocyte subpopulations (CD8+) circulate more frequently during early AF compared with patients without AF and are accompanied by increased levels of plasma CD8 + effector molecules. [18] Activated CD8 + T cells perform by releasing cytotoxins (perforin, granzyme and granulysin) or by releasing the secretion of pro-inflammatory cytokines, such as TNF-α and IFN-γ to induce apoptosis in target cells. [39,40] Peripheral monocytes trigger an inflammatory cascade that releases TGF-β, ROS, complement proteins, and chemokines, ultimately contributing to cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an observational study of 100 consecutive patients, including 80 patients with a first diagnosis of AF and 20 control patients, it was found that pro-inflammatory and cytotoxic T-lymphocyte subpopulations (CD8+) circulate more frequently during early AF compared with patients without AF and are accompanied by increased levels of plasma CD8 + effector molecules. [18] Activated CD8 + T cells perform by releasing cytotoxins (perforin, granzyme and granulysin) or by releasing the secretion of pro-inflammatory cytokines, such as TNF-α and IFN-γ to induce apoptosis in target cells. [39,40] Peripheral monocytes trigger an inflammatory cascade that releases TGF-β, ROS, complement proteins, and chemokines, ultimately contributing to cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[9,[11][12][13][14][15] Previous clinical studies have established a correlation between immunity and AF. [16][17][18] However, the capacity of observational studies to address potential confounding factors and mitigate reverse causality is limited. Mendelian randomization (MR) can be considered as an alternative to randomized controlled trials that use genetic variants to show causality between exposure and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The activation and infiltration of CD8 T cells into the atrial tissue can lead to the release of pro-inflammatory cytokines and chemokines, promoting atrial remodeling and electrical disturbances. This immune response mediated by CD8 T cells may contribute to the perpetuation of AF and its progression to a more chronic and persistent state ( 45 , 46 ). Macrophages contribute to the pathogenesis of AF by releasing pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6, as well as phagocytosing apoptotic cardiomyocytes, which can lead to fibrosis ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“… 5 One study suggests that CD8T cells control monogenesis and macrophage accumulation in early atherosclerosis and play a cytotoxic role therein, and contribute to macrophage death and formation of the necrotic core of the plaque. 6 Another study verified that peroxisome proliferator-activated receptor γ (PPAR γ) can reduce inflammation by activating the recruitment of regulatory T cells. Thus, immune cell infiltration is involved in the occurrence and development of CAD.…”
Section: Introductionmentioning
confidence: 99%